2017
DOI: 10.1016/j.petrol.2017.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Pore pressure effects on fracture net pressure and hydraulic fracture containment: Insights from an empirical and simulation approach

Abstract: A B S T R A C TPore pressure and its relationship with fracture net pressure has been reported qualitatively from both field and experimental observations. From a modeling perspective, the ubiquitously used pseudo 3D (P3D) models that are based on linear elastic fracture mechanics (LEFM) do not include the effect of reservoir depletion (or overpressure). Models that utilize effective stress as propagation criteria with a cohesive zone description, introduce the pore pressure directly into the simulation and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…As previously mentioned, Meyer et al (2017) concluded that pressure drops could be produced by the propagation of tensile fractures as a wing crack. This process could be interpreted in a similar way, as observed in breakdown tests and used to identify the minimum principal stress (Prabhakaran et al 2017). In these tests, the generation of a new hydrofracture produces a pressure drop because the fluid quickly migrates into the newly formed fracture, oriented normal to the minimum stress.…”
Section: Pressure Drop Mechanismmentioning
confidence: 94%
“…As previously mentioned, Meyer et al (2017) concluded that pressure drops could be produced by the propagation of tensile fractures as a wing crack. This process could be interpreted in a similar way, as observed in breakdown tests and used to identify the minimum principal stress (Prabhakaran et al 2017). In these tests, the generation of a new hydrofracture produces a pressure drop because the fluid quickly migrates into the newly formed fracture, oriented normal to the minimum stress.…”
Section: Pressure Drop Mechanismmentioning
confidence: 94%
“…It can be seen from equations (16) and (17) that the value of K I-αp increases as the pore pressure increases, which has a positive e ect on the hydraulic fracture initiation and reduces the required pressure. According to the abovementioned discussion on the stress intensity factors under various cases, the mode-I stress intensity factor caused by the loading conditions in Figure 1 can be evaluated by the sum of equations (1), (7), and (17) as follows:…”
Section: Advances In Materials Science and Engineeringmentioning
confidence: 99%
“…Figure 16(g) shows that the fracture initiation angle increases with the decrease of λ, which suggests the higher the fluid viscosity, the larger the fracture initiation angle. Figure 16(h) indicates that at a given perforation angle, the higher Biot's coefficient, the lower the fracture initiation angle since K I increases as Biot's coefficient increases according to equations (16) and (17). Biot's coefficient is an intrinsic property of rock and is not homogeneous [45]; this inhomogeneity leads to different fracture initiation angles under different stages of the hydraulic fracturing.…”
Section: Effect Of High-pressure Water Injectionmentioning
confidence: 99%
See 2 more Smart Citations